Correlation of cracking behaviour at binder, mastic and asphalt concrete levels. (1st August 2022) - Raab, Christiane; Arraigada, Martin; Ibrahimi, Hamza
Abstract : Some years ago, performance methods for conformity testing of asphalt mixtures were introduced into the European standards defining performance properties such as low temperature resistance, stiffness, resistance to fatigue and permanent deformation. However, such tests are complex and require enormous efforts making it difficult to implement them into routine testing. The research project VEGAS, a collaboration between 3 research institutions from Germany Austria and Switzerland, aimed therefore to simplify the testing system, without sacrificing valuable information. Therefore, testing was reduced to the evaluation of volumetric properties and tests carried out on the binder and mastic only. The paper describes the experimental efforts carried out by Empa in Switzerland, related to low temperature cracking of bitumen and mastic and fatigue experiments on asphalt samples. Within the framework of the research, a new testing procedure using the Double Torsion Test method for low temperature crack propagation in mastic was evaluated. Additionally, asphalt plates were tested with a scaled traffic simulator and used for validating laboratory scale tests.